Pengaruh Komite Audit, Komisaris Independen, Ukuran perusahaan dan Financial Distress Terhadap Integritas Laporan Keuangan - Rembulan Nur Purnamasari; Andri Syahputra (GLOBAL SCIENTS PUBLISHER, 2025)
This study analyzed the influence of the Audit Committee, Independent Commissioners, Company Size, and Financial Distress on Financial Statement Integrity. The study was conducted on infrastructure sector companies listed on the Indonesia Stock Exchange between 2020 and 2024. The methodology used was panel data regression. Purposive sampling was used to select 23 companies, covering a five-year period from 2020 to 2024, resulting in 115 samples. Data were taken from audited financial statements and annual reports published by each company. Hypothesis testing was conducted using Eviews Series 12. The results showed that, partially, the Audit Committee had no effect on Financial Statement Integrity, Independent Commissioners had no effect on Financial Statement Integrity, Company Size had no effect on Financial Statement Integrity, and Financial Distress had a negative effect on Financial Statement Integrity. Simultaneously, the Audit Committee, Independent Commissioners, Company Size, and Financial Distress all had an effect on Financial Statement Integrity.